Clinical communication skills for medicine - Lloyd, Margaret; Bor, Robert; Noble, Lorraine M. (Elsevier Limited, 2019)
The purpose of this book is to produce a practical guide to the learning and development of communication skills that is of value to students throughout their careers. The order of the chapters reflects this development, from basic communication skills to those required in dealing with challenging situations. Since the last edition there has been continuing research in all aspects of communication in medicine and this is reflected both in the text and references. The chapters range from the development of basic skills to those dealing with challenging and difficult situations. For this new edition all of the chapters have been revised and new material added